Hydrotherapy: Warm Water Foot Soak on Lowering Blood Pressure in Hypertensive Patients - Mutmainna, Amriati; Wijayaningsih, Kartika Sari; La Isa, Wamina; Ernawati, Ernawati; Mato, Rusni; Darwis, Darwis; Muzakkir, Muzakkir; Lestari, Suzanty Putri (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Hypertension is a silent disease, because people do not know that they have hypertension before checking their blood pressure. Efforts to treat hypertension can be done with pharmacological and non-pharmacological therapy. Warm water foot soaking is considered a simple and low-cost non-pharmacological therapy with minimal side effects. The aim of this study was to see whether there was an effect of soaking feet in warm water to reduce blood pressure in people with hypertension. This study used a pre-experimental method with a one-group pretest-posttest design. The population in this study were all 48 patients suffering from hypertension in the treatment room. Sampling used the consecutive sampling technique with a total sample of 32 people. Data were collected using observation sheets and analyzed using the Chi-square test and obtained systolic blood pressure with a value of p = 0,036, diastolic blood pressure with a value of p = <0,001. There was an influence of hydrotherapy: soaking feet in warm water to reduce blood pressure in hypertension sufferers at Labuang Baji Hospital, Makassar. It is recommended to soak the feet in warm water in the morning and evening for 15 minutes at a temperature of 37–40°C to achieve optimal results.